The Human PathogenParacoccidioides brasiliensisHas a Unique 1-Cys Peroxiredoxin That Localizes Both Intracellularly and at the Cell Surface - Guilhen Longo, Larissa Valle; Breyer, Carlos Alexandre [UNESP]; Novaes, Gabriela Machado [UNESP]; Gegembauer, Gregory; Leitao Jr, Natanael Pinheiro; Octaviano, Carla Elizabete; Toyama, Marcos Hikari [UNESP]; Oliveira, Marcos Antonio de [UNESP]; Puccia, Rosana (Frontiers Media Sa, 2020)
Paracoccidioides brasiliensisis a temperature-dependent dimorphic fungus that causes systemic paracoccidioidomycosis, a granulomatous disease. The massive production of reactive oxygen species (ROS) by the host's cellular immune response is an essential strategy to restrain the fungal growth. Among the ROS, the hydroperoxides are very toxic antimicrobial compounds and fungal peroxidases are part of the pathogen neutralizing antioxidant arsenal against the host's defense. Among them, the peroxiredoxins are highlighted, since some estimates suggest that they are capable of decomposing most of the hydroperoxides generated in the host's mitochondria and cytosol. We presently characterized a uniqueP. brasiliensis1-Cys peroxiredoxin (PbPrx1). Our results reveal that it can decompose hydrogen peroxide and organic hydroperoxides very efficiently. We showed that dithiolic, but not monothiolic compounds or heterologous thioredoxin reductant systems, were able to retain the enzyme activity. Structural analysis revealed that PbPrx1 has an alpha/beta structure that is similar to the 1-Cys secondary structures described to date and that the quaternary conformation is represented by a dimer, independently of the redox state. We investigated the PbPrx1 localization using confocal microscopy, fluorescence-activated cell sorter, and immunoblot, and the results suggested that it localizes both in the cytoplasm and at the cell wall of the yeast and mycelial forms ofP. brasiliensis, as well as in the yeast mitochondria. Our present results point to a possible role of this uniqueP. brasiliensis1-Cys Prx1 in the fungal antioxidant defense mechanisms.
Keywords: Paracoccidioides brasiliensis; 1-Cys Prx; hydroperoxides; peroxiredoxin; dimorphic fungi; ROS